Synchrotron X‐Ray Scanning Tunneling Microscopy: Fingerprinting Near to Far Field Transitions on Cu(111) Induced by Synchrotron Radiation. (22nd March 2013) - Rose, Volker; Wang, Kangkang; Chien, TeYu; Hiller, Jon; Rosenmann, Daniel; Freeland, John W.; Preissner, Curt; Hla, Saw‐Wai
Abstract The combination of the high spatial resolution of scanning tunneling microscopy with the chemical and magnetic contrast provided by synchrotron X‐rays has the potential to allow a unique characterization of advanced functional materials. While the scanning probe provides the high spatial resolution, synchrotron X‐rays that produce photo‐excitations of core electrons add chemical and magnetic contrast. However, in order to realize the method's full potential it is essential to maintain tunneling conditions, even while high brilliance X‐rays irradiate the sample surface. Different from conventional scanning tunneling microscopy, X‐rays can cause a transition of the tip out of the tunneling regime. Monitoring the reaction of the z‐piezo (the element that controls the tip to sample separation) alone is not sufficient, because a continuous tip current is obtained. As a solution, an unambiguous and direct way of fingerprinting such near to far field transitions of the tip that relies on the simultaneous analysis of the X‐ray‐induced tip and sample current is presented. This result is of considerable importance because it opens the path to the ultimate resolution in X‐ray enhanced scanning tunneling microscopy.